Postpartum depression and autoimmune disease: a bidirectional Mendelian randomization study - Yu, Wenlong; Su, Bingxue; Wang, Chaoqun; Xia, Qing; Sun, Yinxiang (Frontiers in Psychiatry, 2024)
Purpose The rising prevalence of postpartum depression (PPD) is harmful to women and families. While there is a growing body of evidence suggesting an association between PPD and autoimmune diseases (ADs), the direction of causality remains uncertain. Therefore, Mendelian randomization (MR) study was employed to investigate the potential causal relationship between the two. Methods This study utilized large-scale genome-wide association study genetic pooled data from two major databases: the IEU OpenGWAS project and the FinnGen databases. The causal analysis methods used inverse variance weighting (IVW). The weighted median, MR-Egger method, MR-PRESSO test, and the leave-one-out sensitivity test have been used to examine the results’ robustness, heterogeneity, and horizontal pleiotropy. Results A total of 23 ADs were investigated in this study. In the IVW model, the MR study showed that PPD increased the risk of type 1 diabetes (OR , = 1.15 (1.05–1.26),p<0.01),Hashimoto’s thyroiditis((OR) = 1.21 (1.09–1.34),p<0.0001),encephalitis((OR) = 1.66 (1.06–2.60),p<0.05). Reverse analysis showed that ADs could not genetically PPD. There was no significant heterogeneity or horizontal pleiotropy bias in this result. Conclusion Our study suggests that PPD is a risk factor for type 1 diabetes, Hashimoto’s thyroiditis, and encephalitis from a gene perspective, while ADs are not a risk factor for PPD. This finding may provide new insights into prevention and intervention strategies for ADs according to PPD patients.